2015
DOI: 10.1038/srep17798
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Molecule Surfactant Protein D Attenuates Sepsis-induced Acute Pancreatic Injury through Modulating Apoptosis and NF-κB-mediated Inflammation

Abstract: Sepsis causes multiple-organ dysfunction including pancreatic injury, thus resulting in high mortality. Innate immune molecule surfactant protein D (SP-D) plays a critical role in host defense and regulating inflammation of infectious diseases. In this study we investigated SP-D functions in the acute pancreatic injury (API) with C57BL/6 Wild-type (WT) and SP-D knockout (KO) mice in cecal ligation and puncture (CLP) model. Our results confirm SP-D expression in pancreatic islets and intercalated ducts and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 65 publications
(81 reference statements)
2
33
1
Order By: Relevance
“…SP-D can inhibit TLR4 expression and inflammatory cytokines in human corneal epithelial cells through TLR4 signaling pathway during fungal infection [23]. SP-D can inhibit cell apoptosis and modulating NF-κB-mediated inflammation in sepsis-stimulated acute pancreatic injury [11]. The present study is the first to suggest that SP-D expression was observed in chondrocyte, and explain the critical role in modulation of SP-D in OA progression.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…SP-D can inhibit TLR4 expression and inflammatory cytokines in human corneal epithelial cells through TLR4 signaling pathway during fungal infection [23]. SP-D can inhibit cell apoptosis and modulating NF-κB-mediated inflammation in sepsis-stimulated acute pancreatic injury [11]. The present study is the first to suggest that SP-D expression was observed in chondrocyte, and explain the critical role in modulation of SP-D in OA progression.…”
Section: Discussionmentioning
confidence: 62%
“…The structure of SP-D is comprised of four domains, including N-terminus cysteine-rich domain, triple-helical collagen-like domain, neck region and carbohydrate recognition domain (CRD) [6]. Extrapulmonary tissues/organs SP-D expression has been recognized, such as kidney [7], digestive tract and mesentery [8], nasal epithelium [9], salivary glands and saliva [10], pancreas [11], and prostate and reproductive system [12]. Furthermore, SP-D is expressed in the synovial fluid to vary degrees in rheumatoid arthritis (RA), which reveals a characteristic aspect in the pathogenesis of RA as in lung [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et. al using a mouse model of acute pancreatic injury demonstrated that wild type mice had decreased apoptosis and neutrophil infiltration when compared to SP-D knockout mice, demonstrating the protective effect of SP-D (Liu et al, 2015). Saka et al established the protective effect of SP-D in the devastating neonatal intestinal disease, necrotizing enterocolitis (NEC), by establishing that SP-D could attenuate TLR-4 over-expression in immature embryonal intestine cells (Saka et al, 2016).…”
Section: Anti-inflammatory Effects Of Surfactant Collectinsmentioning
confidence: 99%
“…To date, a host of collectins have been described including MBL, SP-A, SP-D, collectin liver 1 (CL-L1), collectin kidney 1 (CL-K1) and conglutinins (Mayer et al, 2017). These collectins recognize and neutralize pathogens by several different mechanisms including aggregation (Tenner et al, 1989), apoptosis (Liu et al, 2015), opsonization (Ferguson et al, 1999; Ghildyal et al, 1999; Hartshorn et al, 1996; Hickling et al, 1999; McIntosh et al, 1996; McNeely and Coonrod, 1994), activation of phagocytosis (Beharka et al, 2002; Ferguson et al, 1999; Nepomuceno et al, 1997; Tenner et al, 1989), inhibition of microbial growth, or modulation of the inflammatory response (Herbein and Wright, 2001; Liu et al, 2015; Saka et al, 2016; Salminen et al, 2008; Sato et al, 2003). Collectins may compete with factors such as LPS for binding to cell surface receptors (Chuang et al, 2011; Ohya et al, 2006; Saka et al, 2016; Vayrynen et al, 2002; Yamada et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been suggested that both the clinical phenotypes are the result of different degree of placental malperfusion and may have different aetiologies. [8][9][10] Collectins, a type of soluble pattern recognition proteins of in- [11][12][13][14] They compete with the inflammatory agents such as LPS for binding to the cell surface receptors and thus feature centrally in the modulation of inflammatory response. Impaired placental development leads to persistent hypoxia at the feto-maternal interface, enhanced release of apoptotic debris in the maternal circulation, and elevation of systemic inflammatory response.…”
mentioning
confidence: 99%